Rihlati ma'a al-jama'ah al-samidah - Abu Shadi, Ahmad (al-Qahirah : Dar al-Tawzi' wa al-Nashr al-Islamiyah, 1998)
Islamic movements; 1951-1965; diaries by an Egyptian member of Brotherhood movement.
Keywords: Jam'iyat al-Ikhwan al-Muslimin (Egypt) -- Biography; Islam and state -- Egypt; Islamic renewal -- Egypt